2007
DOI: 10.1002/biot.200700093
|View full text |Cite
|
Sign up to set email alerts
|

Alternative roles for Cdk5 in learning and synaptic plasticity

Abstract: Protein kinases mediate the intracellular signal transduction pathways controlling synaptic plasticity in the central nervous system. While the majority of protein kinases achieve this function via the phosphorylation of synaptic substrates, some kinases may contribute through alternative mechanisms in addition to enzymatic activity. There is growing evidence that protein kinases may often play structural roles in plasticity as well. Cyclin-dependent kinase 5 (Cdk5) has been implicated in learning and synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…Although CDK5 is ubiquitously expressed, the high neuronal expression of the p35 and p39 implies that CDK5 exerts its major physiologic function in a specific repertoire of tissues, such as the central nervous system. Indeed, previous studies indicated that CDK5 plays a role in a variety of pathologic and physiologic processes associated with neuronal migration during brain development, synaptic activity in mature neurons, and regulation of neuronal cell survival and death (23)(24)(25). Interestingly, these CDK5-dependent functions are unrelated to the regulation of the cell cycle as seen in other CDKs.…”
Section: Introductionmentioning
confidence: 99%
“…Although CDK5 is ubiquitously expressed, the high neuronal expression of the p35 and p39 implies that CDK5 exerts its major physiologic function in a specific repertoire of tissues, such as the central nervous system. Indeed, previous studies indicated that CDK5 plays a role in a variety of pathologic and physiologic processes associated with neuronal migration during brain development, synaptic activity in mature neurons, and regulation of neuronal cell survival and death (23)(24)(25). Interestingly, these CDK5-dependent functions are unrelated to the regulation of the cell cycle as seen in other CDKs.…”
Section: Introductionmentioning
confidence: 99%
“…We used two loss-of-function approaches to show that Cdk5 activity is essential for cLTP-induced TrkB surface insertion: pharmacological inhibition of Cdk5 and siRNA knock-down of Cdk5 levels. Cdk5 has been shown to play an important role in synaptic plasticity (Angelo et al, 2006;Cheung et al, 2006;Hawasli and Bibb, 2007). Recently, it has been reported that Cdk5 could directly phosphorylate TrkB and is involved in BDNF-stimulated dendritic growth in hippocampal neurons (Cheung et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, many Cdks are expressed in terminally differentiated neurons (57)(58)(59)(60)(61), and furthermore, Cdk5, the sole non-cyclin-activated member of the Cdk family, has been shown to regulate synaptic plasticity and learning (62)(63)(64)(65)(66)(67). Notably, neither SU-9516 nor its primarily characterized target, Cdk2, has been implicated in synaptic plasticity or learning.…”
Section: Conservation Of Neural Substrates Of Learning Between Zebrafmentioning
confidence: 92%